Precarious engagements and the politics of knowledge production: Listening to calls for reorienting hegemonic social psychology. (20th December 2022) - Reddy, Geetha; Amer, Amena
Abstract: In this paper, we invite psychologists to reflect on and recognize how knowledge is produced in the field of social psychology. Engaging with the work of decolonial, liberation and critical psychology scholars, we provide a six‐point lens on precarity that facilitates a deeper understanding of knowledge production in hegemonic social psychology and academia at large. We conceptualize knowledge (re)production in psychology as five interdependent 'cogs' within the neoliberal machinery of academia, which cannot be viewed in isolation; (1) its epistemological foundations rooted in coloniality, (2) the methods and standards it uses to understand human thoughts, feelings and behaviours, (3) the documentation of its knowledge, (4) the dissemination of its knowledge and (5) the universalization of psychological theories. With this paper we also claim our space in academia as early career researchers of colour who inhabit the margins of hegemonic social psychology. We join scholars around the world in calling for a much‐needed disciplinary shift that centres solutions to the many forms of violence that are inflicted upon marginalized members of the global majority. To conclude, we offer four political‐personal intentions for the reorientation for the discipline of hegemonic social psychology with the aim to disrupt the politics of knowledge production and eradicate precarity.